SYNTHETIC LYCOPENE: THE FUTURE BUT UNAWARE FACT - Chatterjee, Bandana (International Journal of Clinical and Biomedical Research, 2016)
Food color is used as a food additive. A color additive is any dye, Pigment or substance. Mainly two type of food colors are used in food Industry: Natural and Artificial. There are 26 colors which are permitted to be used in food. A few Natural colors mainly used are Annatto,turmeric, Lycopene, Beet root and caramel etc. Lycopene is processed from Tomatoes and widely used. In this short communication we wanted to create a awareness about synthetic lycopene and their properties. KEYWORDS: Annatto, Turmeric, Lycopene, Beet root; Caramel.